X-ray Analysis of ZnO Nanoparticles by Williamson-Hall and Size-Strain Plot Methods - Khorsand Zak, A.; Abd Majid, Wan Haliza; Abrishami, M.E.; Yousefi, R. (2011)
ZnO nanoparticles (ZnO-NPs) were prepared by a sol-gel combustion method from a zinc acetate precursor and acetic acid. The ZnO-NPs were synthesized at calcination temperatures of 650 °C and 750 °C for 1 h. The synthesized ZnO-NPs were characterized by X-ray diffraction analysis (XRD) and TEM. The XRD results revealed that the sample product was crystalline with a hexagonal wurtzite phase. High-magnification transmission electron microscopy (TEM) showed single-crystal ZnO-NPs with nearly spherical shapes. The crystalline development in the ZnO-NPs was investigated by X-ray peak broadening. The Williamson-Hall (W-H) analysis and size-strain plot method were used to study the individual contributions of crystallite sizes and lattice strain on the peak broadening of the ZnO-NPs. The physical parameters such as strain, stress and energy density values were calculated more precisely for all the reflection peaks of XRD corresponding to the wurtzite hexagonal phase of ZnO lying in the range of 20°-100° from the modified form of the W-H plot assuming a uniform deformation model (UDM), uniform stress deformation model (USDM), uniform deformation energy density model (UDEDM) and by the size-strain plot method (SSP). The results obtained showed that the mean particle size of the ZnO-NPs estimated from the TEM, W-H analysis and the SSP method were highly intercorrelated. © 2010 Elsevier Masson SAS. All rights reserved.